2001
DOI: 10.4049/jimmunol.167.7.3972
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylatoxin C5a Actions in Rat Liver: Synergistic Enhancement by C5a of Lipopolysaccharide-Dependent α2-Macroglobulin Gene Expression in Hepatocytes Via IL-6 Release from Kupffer Cells

Abstract: The effects of the anaphylatoxins C5a and C3a on the liver are only poorly characterized in contrast to their well known systemic actions. Recently, it has been demonstrated that the anaphylatoxin C5a enhanced glucose output from hepatocytes (HC) indirectly via prostanoid release from Kupffer cells (KC). In the present study, it is shown that recombinant rat C5a (rrC5a), together with LPS, activated the gene of the acute phase protein α2-macroglobulin (α2MG) in HC also indirectly via IL-6 release from KC. RrC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
(45 reference statements)
2
23
1
3
Order By: Relevance
“…These substances elicited effector functions of hepatocytes only indirectly by means of intercellular communication (Hespeling et al, 1995;Mäck et al, 2001;Püschel et al, 1996;Schieferdecker et al, 1999). In agreement with these observations, putative receptors for C5a and zymosan were predominantly or even exclusively expressed by KCs but not or only scarcely by hepatocytes (Fig.…”
Section: Involvement Of Putative C5a and Zymosan Receptors In The Intsupporting
confidence: 75%
See 1 more Smart Citation
“…These substances elicited effector functions of hepatocytes only indirectly by means of intercellular communication (Hespeling et al, 1995;Mäck et al, 2001;Püschel et al, 1996;Schieferdecker et al, 1999). In agreement with these observations, putative receptors for C5a and zymosan were predominantly or even exclusively expressed by KCs but not or only scarcely by hepatocytes (Fig.…”
Section: Involvement Of Putative C5a and Zymosan Receptors In The Intsupporting
confidence: 75%
“…5). However, this faint mRNA expression in hepatocytes obviously did not lead to the expression of functional C5L2 protein, because under normal conditions hepatocytes did not respond to C5a (Hespeling et al, 1995;Mäck et al, 2001;Schlaf et al, 1999) nor to C5adesarg (unpublished observations).…”
Section: Involvement Of Putative C5a and Zymosan Receptors In The Intmentioning
confidence: 99%
“…A by-product of complement activation, the complement factor 5a (C5a), is a potent pro-inflammatory mediator during I/R injury in various organs [9 -13]. Activation of C5a receptors on PMNs leads to chemotaxis, expression of cellular adhesion receptors, release of pro-inflammatory mediators [14 -16] and release of pro-inflammatory cytokines from Kupffer cells [17]. Experimental studies have shown that blockade of complement activation results in improved microcirculation [8] and reduced leukocyte adherence [18] following hepatic I/R.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting with a lack of C5aR expression on normal rat hepatocytes, C5aR expression has been observed at both mRNA and protein levels under inflammatory conditions, i.e., in IL-6-challenged rats (9). Likewise, recombinant rat C5a, together with LPS, activates the ␣ 2 -macroglobulin gene (coding for an APP) in rat hepatocytes (10). Recently, complement has been considered as a regulator of cell proliferation and differentiation during development (11,12), and in this context, has been suggested to play novel roles as a regulator of noninflammatory processes.…”
mentioning
confidence: 99%